الفروق فى أبعاد الكفاءة الذاتية المدركة فى تدريس الاقتصاد المنزلى لتلميذات المرحلة الإعدادية - عسكر، نجلاء عبدالبر عبدالسميع; نوير، مها فتح الله بدير; غنيم، محمد عبدالسلام سالم (جامعة عين شمس - كلية التربية - الجمعية المصرية للقراءة والمعرفة, 2018)
الفروق في أبعاد الكفاءة الذاتية المدركة في تدريس الاقتصاد المنزلي لتلميذات المرحلة الإعدادية" أهداف البحث: 1. تدريس وحدتين من مقرر الاقتصاد المنزلي للصف الأول الإعدادي باستخدام الكفاءة الذاتية المدركة. 2. التعرف على الفروق في أبعاد الكفاءة الذاتية المدركة. عينة البحث: تكونت عينة البحث من (62) تلميذة، حيث يمثل المجموعة التجريبية (31) تلميذة، فصل يمثل المجموعة الضابطة وقوامه (31) تلميذة منهج البحث: استخدم البحث المنهج شبه التجريبي. أدوات البحث: يتم استخدام الأدوات التالية لقياس متغيرات البحث: - اختبار الكفاءة الذاتية المدركة (إعداد الباحثة) أهم نتائج البحث: وجود فروق ذات دلالة إحصائية بين متوسطي درجات تلميذات المجموعة التجريبية في التطبيق البعدي في كل بعد من أبعاد الكفاءة الذاتية المدركة (البعد السلوكي، البعد الاجتماعي، البعد المعرفي الأكاديمي، البعد الانفعالي، بعد الإصرار والمثابرة) وفي الاختبار الكلي للكفاءة الذاتية المدركة لصالح المجموعة التجريبية، مما يدل على مراعاة الفروق في أبعاد الكفاءة الذاتية المدركة لتلميذات الصف الأول الإعدادي من خلال تدريس الاقتصاد المنزلي.
Differences in the dimensions of perceived self-efficacy in teaching home economics to junior high school girls". Research goals: 1. Teach two units of the decision of Home Economics, first grade middle school using the perceived self-efficacy. 2. To identify the differences in the perceived self-efficacy dimensions. The research sample: The research sample consisted of 62 pupils, where an experimental group (31) schoolgirl, separation represents a control group and texture (31) schoolgirl. Research Methodology: Use the search quasi-experimental approach. Search tools: The following tools are used to measure the research variables: - Perceived self-efficacy test (the researcher). The most important results of the search results: There are statistical significance between the mean differences grades pupils of the experimental group in the post application in every dimension of self-efficacy perceived (behavioral dimension, the social dimension, the dimension Cognitive Academic, dimension and emotional, after Alaasraroualemthabrh) and kidney test of the efficiency of self-conscious for the experimental group, which It shows considerate to differences in the perceived self-efficacy for first grade students from middle school through the teaching of home Economics dimensions.
Keywords: الكفاءة الذاتية -- تدريس الاقتصاد المنزلى -- المرحلة الإعدادية